Computational investigations of the band structure, and thermodynamic and optical features of thorium-based oxide ThGeO4 using the full-potential linearized augmented plane-wave plus local orbital approach. (May 2018) - Chiker, F.; Khachai, H.; Mathieu, C.; Bin-Omran, S.; Kada, Belkacem; Sun, Xiao-Wei; Sandeep,; Rai, D.P.; Khenata, R.
Abstract: In this study, first-principles investigations were performed using the full-potential linearized augmented plane-wave method of the structural and optoelectronic properties of thorium germinate (ThGeO4 ), a high-K dielectric material. Under ambient conditions, the structural properties calculated for ThGeO4 in the zircon phase were in excellent agreement with the available experimental data. Furthermore, using the modified Becke -Johnson correction method, the calculated band gaps and optical constants accurately described this compound. Finally, the thermal properties were predicted over a temperature range of 0–700 K and pressures up to 11 GPa using the quasi-harmonic Debye model, where the variations in the heat capacity, primitive cell volume, and thermal expansion coefficients were determined successfully. Highlights: Interesting physical properties of ThGeO4 were investigated. ThGeO4 is a wide band gap semiconductor. Electronic and optical constants indicate possible use as anti-reflective coating. Optical and thermodynamic properties of ThGeO4 studied for the first time.